Estudio de situación socio - lingüística del kichwa en la comunidad de Pitaná Bajo de la parroquia de Cangahua - Conterón Morán, Galo Enrique (2015)
This thesis is a study of the socio-linguistic situation of the Kichwa community of Pitana Under Cangahua Parish. There is research to know how much they know about the Kichwa community, guides, observation was conducted through surveys, interviews, each group was observed that over time the Kichwa language daily has been lost. Although the State told the Quechua language as the official language communities are forgetting her language and customs, traditions, festivals and clothing. Of the total population, there 8 person older than 68 years who speak and understand the Kichwa. Then research has a purpose; collaborate and contribute in their recovery, through incentives and encouragement to family and school children, who are most suitable to begin the revitalization of it. The Kichwa is an ancient language whose original writing is unknown, therefore, have used the Castilian graphs to represent the characteristic sounds of the language in question. The Kichwa has different dialects according to the locality where it is spoken (phonology of consonants and use of certain words), for this reason and due to the use of Castilian spellings for writing, there were different ways of representing the same word According to the way it sounded.